HUBUNGAN KREATIVITAS GURU BERDASARKAN PERSEPSI SISWA DENGAN MINAT BELAJAR MATA PELAJARAN KECANTIKAN DASAR SISWA KELAS X KC SMK NEGERI 7 PADANG - Septi Harpina; Rahmiati Rahmiati (Universitas Negeri Padang, 2022)
This research aims to: a) describe teacher creativity based on student perception, b) describe students' learning interests c) describe the relationship of teacher creativity based on the perception of students with the interest of students of basic beauty subjects of grade X students of Grade X KC SMK Negeri 7 Padang. This type of research is quantitative research with a cholerasional approach. The research population is grade X students of SMK Negeri 7 Padang majoring in Makeup and Beauty which numbered 88 people consisting of 3 classes, the technique of displaying cluster samples from 3 classes taken two classes for a sample while one class was made for instrument trials. Data retrieval technique is to use questionnaires. Data analysis techniques using correlation test and t test. Based on the results of the respondent's achievement level in the student creativity based on student perception of 76.02% moderate category, the respondent's attainment rate in the interest of learning is 77.35% of the moderate category and there is a relationship between the creativity of the teacher based on the perception of the student and the interest in learning the basic beauty subjects of grade X students KC SMK Negeri 7 Padang. t hitung > t tabel 2,811 >2,003 with a coefficient value(r) = 0.334